2007
DOI: 10.1111/j.1600-0684.2007.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Barbiturate euthanasia solution‐induced tissue artifact in nonhuman primates

Abstract: When the recommended dose of agent was used, tissue damage was generally reduced, minimal, or undetectable. Barbiturate-induced artifacts in NHPs are essentially the same as in other laboratory species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…This method is approved by the American Veterinary Medical Association. We have demonstrated fewer tissue artifacts following exsanguination than following administration of euthanasia solutions, which produce marked histological changes, especially in the liver (Grieves et al 2008). The placenta and fetus were removed from the uterus and immediately submitted for morphometric measurements including fetal and liver weight, complete pathological evaluation, and tissue sampling.…”
Section: Methodsmentioning
confidence: 93%
“…This method is approved by the American Veterinary Medical Association. We have demonstrated fewer tissue artifacts following exsanguination than following administration of euthanasia solutions, which produce marked histological changes, especially in the liver (Grieves et al 2008). The placenta and fetus were removed from the uterus and immediately submitted for morphometric measurements including fetal and liver weight, complete pathological evaluation, and tissue sampling.…”
Section: Methodsmentioning
confidence: 93%
“…This change has been made since we have demonstrated fewer tissue artefacts following exsanguination than following administration of euthanasia solutions, which produce marked histological changes, especially in the liver (Grieves et al . ). Morphometric measurements were collected and tissue samples obtained immediately after the placenta and fetus were removed from the uterus.…”
Section: Methodsmentioning
confidence: 97%
“…This method is approved by the American Veterinary Medical Association. Previous study has demonstrated fewer tissue artifacts after exsanguination than after administration of euthanasia solutions (33). Maternal and fetal blood was collected from the femoral artery and umbilical vein, respectively.…”
Section: Methodsmentioning
confidence: 99%